The Victorian Early Years Learning and Development Framework: Managing Change in a Complex Environment. Issue 2 (June 2013) - Garvis, Susanne; Pendergast, Donna; Twigg, Danielle; Flückiger, Bev; Kanasa, Harry; Phillips, Carmel; Bishop, Maggie; Lockett, Kerryn; Leach, Darlene
THIS ARTICLE REPORTS ON an Educational Change Model originally developed for the middle years of schooling (Pendergast et al., 2005) and applied here to an Australian early childhood education reform initiative. The Victorian Early Years Learning and Development Framework (VEYLDF) was released in 2009 (DEECD & VCAA, 2009). Implementation of the VEYLDF was accompanied by a three-stage independent evaluation on early childhood professionals perceptions of implementation. According to the Educational Change Model, three distinct phases can be identified as individuals and groups move towards full implementation of reforms. The phases are: Initiation, Development, and Consolidation. Evaluation of initiatives delivered in the implementation of the VEYLDF against key elements of the Educational Change Model revealed that: critical model elements of visioning, policy development, stakeholder engagement and information dissemination were achieved at a high level; resources were developed for early childhood professionals to implement in a range of formats and mediums; the importance of leadership in educational change was recognised in the VEYLDF implementation; inhibitors and enablers to the implementation of the VEYLDF were identified in anticipation of the Development phase of the Educational Change Model. The staged implementation of the VEYLDF provided opportunities for progressive feedback on implementation successes and challenges.